Evaluation of postural stability under single and dual task conditions in individuals with and without intellectual disability. - Gutiérrez-Cruz, Carmen; Muñoz-López, Saray; Ruiz-Perálvarez, Francisco J.; Janicijevic, Danica (International Journal of Developmental Disabilities, 2025)
Background: The aim was to investigate how varying levels of intellectual disability (ID) impact postural stability parameters and response reaction time (RRT). Method: Fifty-nine individuals with low and moderate levels of ID and 55 sex- and age-matched peers without ID performed a bipedal standing postural control task while having their (I) eyes open [OE], (II) eyes closed [CE], and (III) while performing a secondary cognitive task- pressing a trigger button while maintaining still stance (dual task, DT). Seven postural control parameters (total, mediolateral and anteroposterior displacement, sway area, sway mean velocity, mediolateral dispersion, and anteroposterior dispersion) during each experimental condition as well as the RRT during the DT were recorded. Results: The results revealed that (I) CE and DT partially affected postural control parameters when compared to OE condition (in 13 and in 3 out of 21 pairwise comparisons, respectively), (II) individuals with ID had poorer postural control than peers without ID during the OE and DT conditions (p ≤ 0.05), but not during the CE condition (except for the larger total displacement observed in participants with moderate disability compared to participants without ID, p ≤ 0.05), (III) RRT was longer in individuals with ID compared to the group without ID (p ≤ 0.001), and (IV) no postural control parameter (p ≥ 0.05) nor RRT (p = 0.138) revealed differences between the participants with low and moderate levels of ID. Conclusions: These findings suggest that individuals with ID present reduced performance in the postural control parameters especially when they need to respond to DT compared to individuals without ID.